Household renovation before and during pregnancy in relation to preterm birth and low birthweight in China. (22nd January 2019) - Liu, Wei; Huang, Chen; Li, Baizhan; Zhao, Zhuohui; Yang, Xu; Deng, Qihong; Zhang, Xin; Qian, Hua; Sun, Yuexia; Qu, Fang; Wang, Lifang; Lin, Zhijing; et al.
Abstract: From October 2010 to April 2012, we conducted a cross‐sectional study of associations between household environments and childhood health among preschool children in eight Chinese cities. Here, we analyze associations of early household renovation with preterm birth (PTB), low birthweight (LBW), term low birthweight (Term‐LBW), and small for gestational age (SGA). Parents responded to questions about household renovation and their children's gestational age and birthweight. In the multivariate logistic regression analyses, household renovation in the year before pregnancy was significantly associated with LBW (sample size: N = 25 813; adjusted odds ratio (OR) with 95% confidence intervals (CIs): 1.23, 1.01‐1.50) and Term‐LBW (N = 24 823; 1.29, 1.01‐1.67). Household renovation during pregnancy was significantly associated with PTB (N = 25 202; 1.28, 1.01‐1.69). These significant associations were also found in the two‐level (city‐child) logistic regression analyses and in the sensitivity analyses among 21 009 children with complete data in all studied variates. Stronger associations were found in certain subgroups. Our findings indicate that household renovation within one year before pregnancy might be a risk factor for LBW and Term‐LBW, while household renovation during pregnancy could be a risk factor for PTB.